Perumusan Strategi Pengembangan Usaha Mikro oleh Dinas Koperasi Usaha Kecil Menengah dan Perdagangan Kabupaten Ciamis - Andin Siryatin Zulfa; Arie Budiawan; Ii Sujai (Universitas 17 Agustus 1945 Semarang, Indonesia, 2024)
The problem phenomenon faced by Micro Businesses is the limited ability to enter a larger and wider trade chain system, so that opportunities to develop are limited both in terms of market competition and business product innovation. The aim of the research is to carry out an analysis of the Formulation of Micro Business Development Strategies by the Ciamis Regency Small and Medium Enterprises Cooperatives and Trade Service. The method uses a descriptive qualitative research design, by obtaining data from the results of field studies and literature studies. Data analysis using data reduction, data display, and conclusion drawing/verification. The results of the research show that the formulation of the Micro Business Development Strategy by the Ciamis Regency Small and Medium Enterprises Cooperatives and Trade Service has not been implemented optimally, because there are problems with data on Micro Business actors in Ciamis Regency which have not produced accurate data. Officers are limited in carrying out Micro Business development because it is not proportional to the number of Micro Business actors. The management budget for empowering micro businesses is less than the budget for facilitating business permits.